Medical encounters at community-based physical activity events (parkrun) in the UK. Issue 24 (4th August 2021) - Pedlar, Charles R; Myrissa, Kyriaki; Barry, Megan; Khwaja, Iman G; Simpkin, Andrew J; Newell, John; Scarrott, Carl; Whyte, Greg P; Kipps, Courtney; Baggish, Aaron L
Abstract : Objective: To determine the incidence, clinical correlates and exposure risk of medical encounters during community-based physical activity events in the UK. Methods: An analysis of medical data from weekly, community-based physical activity events (parkrun) at 702 UK locations over a 6-year period (29 476 294 participations between 2014 and 2019) was conducted in order to define the incidence and clinical correlates of serious life-threatening, non-life-threatening and fatal medical encounters. Results: 84 serious life-threatening encounters (overall incidence rate=0.26/100 000 participations) occurred including 18 fatalities (0.056/100 000 participations). Statistical modelling revealed that the probabilities of serious life-threatening encounters were exceptionally low, however, male sex, increasing age, slower personal best parkrun time and less prior running engagement/experience (average number of runs per year and number of years as a parkrun participant) were associated with increased probability of serious life-threatening encounters. These were largely accounted for by cardiac arrest (48/84, 57%) and acute coronary syndromes (20/84, 24%). Non-life-threatening medical encounters were mainly attributed to tripping or falling, with a reported incidence of 39.2/100 000 participations. Conclusions: Serious life-threatening and fatal medical encounters associated with parkrun participation are extremely rare. In the context of a global public health crisis due to inactivity, this finding underscores the safety and corollary public health value of community running/walking events as a strategy to promote physical activity.